CALIDAD DE ATENCIÓN EN EL SERVICIO Y SU RELACIÓN CON LA SATISFACCIÓN DE LOS USUARIOS EN LA OFICINA REGIONAL DE OSINERGMIN LA LIBERTAD 2015 - Comeca Castillo, Jhajaira Estephany (2016)
This research has been prepared in order to meet quality care services and its relationship with user satisfaction in office Osinergmin general themes based on quality, service and customer satisfaction. Currently the key to competitive advantage lies in delivering high quality services that result in satisfied customers. So the quality of service was created to differentiate and add value to the service offerings. This report has been developed with a contrasting descriptive design, methods that have been applied were: inductive and deductive method; and research and technical surveys were applied to users. In surveys of users, we can highlight that the treatment, the friendliness and the standby time is the most valued attributes. However, there are criteria for improvement, such as security, infrastructure and the use of information material to support care. After this research we can conclude that the quality of care has a positive impact on user satisfaction Osinergmin- office Trujillo.